The Human Beings’ Submissiveness to Supernatural Beings in Folktales from Central Sulawesi - Simon Arsa Manggala (Program Studi Magister Ilmu Linguistik Universitas Warmadewa, 2023)
Indonesia is an archipelagic nation of thousands of islands with vast and diverse cultures. Every inhabited island must have at least a culture comprising cultural products such as rites, tales, ceremonies, etc. However, some individual islands might also have more than one culture. The culture carries sets of beliefs that are worth examining to understand and cultivate the people’s worldviews and perspectives. Those perspectives can be traced from folktales as cultural products. As the agent in the Anthropocene period, human beings are also observable in the generationally told folktales. This article explores the depictions and the roles of human characters and supernatural beings in two folktales from Sulawesi, one of the biggest islands in Indonesia. It problematizes the independency and power of human beings in the folktales. The research objects of this article are The Giant and the Orphan (Kalamboro Kaa Elu-elu) and People Who Descended (Miantii). By employing appraisal theory (Martin and White, 2005), this article identifies the attitudes towards both human and supernatural characters by the linguistic choices attached to them in the folktales. The choices of words and expressions depicting the characters are classified into affect, judgement, and appreciation. In conjunction with the folktales’ plot, the linguistic analysis reveals that human characters in those two folktales are depicted as dependent on and powerless before supernatural characters. This article does not intend to draw any generalization toward any cultures from Sulawesi and Indonesia since it examines very limited objects.